Bibliografi Beranotasi Skripsi Bertajuk Islam di Minangkabau Tahun 1982-2012 Koleksi Perpustakaan Fakultas Adab IAIN Imam Bonjol Padang - Sari, Evi Novita; Nelisa, Malta (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2013)
The purposes of this study wereÂ to (1) to describe the creation of descriptive enumerative bibliography thesis titled Islam in Minangkabau in 1982-2012 as one of the search tools or referral information in the library of the Faculty of Adab IAIN Imam Bonjol Padang; (2) describes the obstacles encountered in the manufacture of enumerative bibliography descriptive thesis titled Islam in Minangkabau years 1982-2012 Faculty library collection Adab IAIN Imam Bonjol Padang; (3) describes a solution to overcome the obstacles encountered in the manufacture of enumerative bibliography descriptive thesis titled Islam in Minangkabau years 1982-2012 Faculty library collection Adab IAIN Imam Bonjol Padang. This paper contains an annoted bibliography by subject manufacture thesis titled Islam in Minangkabau. Data were collected through observation and direct observation in the library Faculty library collection Adab IAIN Imam Bonjol Padang. Analyzing the data be descriptive. Keywords: annotated bibliography, thesis titled Islam in Minangkabau collection